Peripheral hypoarousal but not preparation-vigilance impairment endures in ADHD remission - James, Sarah-Naomi; Cheung, Celeste H. M.; Rommel, Anna-Sophie; McLoughlin, Grainne; Brandeis, Daniel; Banaschewski, Tobias; Asherson, Philip; Kuntsi, Jonna (Journal of attention disorders, 2020)
Objective:This study investigates whether impairments associated with persistent ADHD-impaired attention allocation (P3 amplitude), peripheral hypoarousal (skin conductance level [SCL]), and adjustment in preparatory state (contingent negative variation [CNV])-reflect enduring deficits unrelated to ADHD outcome or are markers of ADHD remission.Method:Young people with childhood ADHD (73 persisters and 18 remitters) and 144 controls were compared on neurophysiological measures during two conditions (baseline and fast-incentive) of a four-choice reaction time task.Results:ADHD remitters differed from persisters, and were indistinguishable from controls, on baseline P3 amplitude and fast-incentive CNV amplitude (p <= .05). ADHD remitters differed from controls (p <= .01), and were indistinguishable from persisters (p> .05), on baseline SCL.Conclusion:Preparation-vigilance measures were markers of ADHD remission, confirming previous findings with other measures. Yet, SCL-measured peripheral hypoarousal emerges as an enduring deficit unrelated to ADHD improvement. Future studies should explore potential compensatory mechanisms that enable efficient preparation-vigilance processes in ADHD remitters.